2020
DOI: 10.1016/j.asmr.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical Properties of a High-Tensile Strength Tape for Tendon Graft Fixation Using the Krackow Configuration

Abstract: To compare the biomechanical properties of a high-tensile strength suture with the high-tensile strength tape for tendon graft fixation. Methods: A total of 24 porcine tendons were used and were randomly divided into 2 groups. Two kinds of suture materials, a braided nonabsorbable high-strength suture (group S) and a high-tensile strength tape (group T), were used to complete 3 pairs of Krackow stitches on the tendons. Each specimen was pretensioned to 100 N for 3 cycles, cyclically loaded from 50 to 200 N for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…The present study further investigated the biomechanical properties of the round suture and tape in arthroscopic sliding knots and demonstrated greater clinical failure loads in the tape samples than in the round suture samples. These findings are consistent with the reports of prior works 7 , 10 and support the use of tapes in arthroscopic surgeries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study further investigated the biomechanical properties of the round suture and tape in arthroscopic sliding knots and demonstrated greater clinical failure loads in the tape samples than in the round suture samples. These findings are consistent with the reports of prior works 7 , 10 and support the use of tapes in arthroscopic surgeries.…”
Section: Discussionsupporting
confidence: 92%
“…They also indicated that high-strength tape showed superior knot security with minimal slippage compared with high-strength round sutures even though the average knot stack height for both tape and round sutures was comparable. 10 Hong et al 7 compared the No. 2 high-strength round suture and 1.3-mm high-strength tape applied for tendon graft fixation using a Krackow configuration and found a greater ultimate failure load in the high-strength tape group.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] On the other hand, tapetype sutures were developed to prevent sutures from pulling through the tendons and were believed to provide greater tendon graft fixation strength compared to round-shaped sutures. [17][18][19] However, it remains unclear whether tapetype sutures can provide superior biomechanical properties in tendon graft fixation using needleless suture wrapping techniques. The present study then further investigated the use of tape-type suture in tendon graft fixation using needleless suture wrapping techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical testing parameters and testing protocol were in accordance with those used in previous studies. 2,6,12,15,16,19,21,23,26,27 Initially, three cycles of pretensioning force ranging from 0 to 100 N at a rate of 100 mm/min were conducted. After preloading to 50 N for 1 minute, each specimen was cyclically loaded between 50 and 200 N with a cross-head speed of 200 mm/min for 200 cycles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation